Customer Loyalty in Indonesian Sharia Commercial Banks: Study of Customer Satisfaction and Service Quality as Moderating Variables - Bakti Setyadi, Bakti Setyadi; Sulaiman Helmi; Syed Ismail bin Syed Mohammad (International Journal of Islamic Business and Economics (IJIBEC), 2023)
Providing quality services is one strategy to achieve business success in the service sector, especially in terms of customer satisfaction and loyalty. This study aims to understand the empirical model and analyze the impact of service quality on customer loyalty, mediated by customer satisfaction. To achieve this, an explanatory research design was used, and a sample of 150 customers from the Palembang branch of Islamic Banks was selected using a simple random sampling technique. A questionnaire was used as the research instrument, and its validity and reliability were tested using CFA analysis. A complex causality model was then used, which was tested through the PLS-SEM technique. The results revealed that service quality has a significant direct effect on customer loyalty, with a substantial immediate impact on customer satisfaction. Additionally, customer satisfaction partially mediates the impact of service quality on customer loyalty. These findings have significant implications for businesses in the service sector, indicating that providing quality services is a critical strategy for achieving success, particularly in terms of customer satisfaction and loyalty. Based on these results, it is suggested that businesses focus on improving the quality of their services by regularly monitoring and assessing the quality of services offered to customers and investing in employee training to enhance the quality of their services.